Investigation of the Impact Properties of Reactive Powder Concrete Containing Nano-Silica and Reinforced with Fibers under Repeated Drop-Weight Impact - ZanganehZadeh, Kiana; Jamshidi, Morteza (Management Strategies and Engineering Sciences, 2025)
Given the increasing demand for high-performance and sustainable construction materials, reactive powder concrete (RPC) has attracted significant attention from researchers due to its exceptional mechanical properties. In this study, the interactive effects of nano-silica (at 0%, 0.5%, and 1% by weight of cement), fiber type (steel and polypropylene), fiber content (0%, 1%, and 2% by volume), and curing method on the impact resistance of RPC were investigated. RPC samples were produced with various nano-silica and fiber contents and subjected to three different curing methods: standard moist curing for 28 days, thermal curing in hot water at 90°C for 2 and 5 days followed by standard moist curing until 28 days of age. The results of the drop-weight impact tests showed that steel fibers significantly improved the initial and final impact resistance of RPC, whereas polypropylene fibers had a lesser effect on these parameters. Additionally, the incorporation of nano-silica and thermal curing marginally enhanced the impact performance of RPC. Statistical analysis of the data using the two-parameter Weibull distribution indicated that this distribution is a suitable model for describing the failure behavior of RPC under impact loading.